Multisector, multilevel stakeholderʼs perspectives of the adolescent girls’ HPV vaccination program in Colombia: an exploratory qualitative service evaluation (2023)
ABSTRACT: Introduction and purpose Current policy for HPV vaccine in Colombia is to vaccinate 9-16 years old girls with 2-dose series thru a school-based vaccination program. HPV vaccination rates dropped from 88% in 2012 to 36.2% in 2021 after a massive psychogenic event in 2014 in Carmen de Bolívar, a town of the north region of Colombia. We conducted an exploratory evaluation process to plan an implementation research project to identify barriers and facilitators for HPV vaccination in Colombia. Methods Funding source: Findings Conclusions Table 2. Participants in the Focus groups Table 1. Key Informant Interviews (KII) The policy for an exclusive school-based program, the lack of operational guidelines adapted to local context and inadequate planning of HPV vaccine supply were factors perceived by the Key informants as barriers for the HPV vaccination. The little multisectoral (health, education and communities) articulation was a factor perceived as a barrier by KIIs and participants of the FGs. The information collected is being used to co-design with stakeholders an implementation research project that will aim at identifying barriers and facilitators for HPV vaccine uptake at state level scale. Low awareness for children good health Carmen de Bolívar Psychogenic event Barriers Not information about the process of consent Not timely vaccine availability FG2 Not training Understaffed FG2 Inefficient information systems Family unaware of benefits of vaccine Little supplier commitment Different perceptions about sexuality Parent´s and teacher´s myths about the HPV vaccine Vaccination at providers sites beside schools Vaccination at schools Facilitators Informed Consent Articulation between the health and education sectors FG1 Promotion of sexual health education Main barriers and facilitators identified in the focus groups Main domains and constructs of the CFIR identified in the KIIs. Objective: To conduct an exploratory evaluation process to plan and inform the design and identification of stakeholders for an implementation research project aimed at identifying barriers and facilitators for HPV vaccination in Colombia. Setting: National (Colombia), State (Antioquia) and Local (Copacabana) organizations responsible of the national HPV vaccination program. Sampling: Purposeful sampling by snowball. Data collection: 4 Key informant interviews (KIIs) guided by some a priori determined constructs of the Consolidated Framework for Implementation Research (CFIR). 4 Focus groups (FG) with participants engaged by researcher. Analysis: conducted independently by at least 2 researchers (1 experienced and 1 recently trained). Each KII was coded by applying predetermined categories of the CFIR. Codes were developed from participants’ own words, and constant comparative analysis for FG.